Inhibition of [FeFe]-hydrogenase by formaldehyde: proposed mechanism and reactivity of FeFe alkyl complexes. Issue 47 (22nd November 2021) - Zhang, Fanjun; Woods, Toby J.; Zhu, Lingyang; Rauchfuss, Thomas B.
Abstract : The mechanism for inhibition of [FeFe]-hydrogenases by formaldehyde is examined with model complexes. Abstract : The mechanism for inhibition of [FeFe]-hydrogenases by formaldehyde is examined with model complexes. Key findings: (i) CH2 donated by formaldehyde covalently link Fe and the amine cofactor, blocking the active site and (ii) the resulting Fe-alkyl is a versatile electrophilic alkylating agent. Solutions of Fe2 [(μ-SCH2 )2 NH](CO)4 (PMe3 )2 (1 ) react with a mixture of HBF4 and CH2 O to give three isomers of [Fe2 [(μ-SCH2 )2 NCH2 ](CO)4 (PMe3 )2 ] + ([2 ] + ). X-ray crystallography verified the NCH2 Fe linkage to an octahedral Fe(ii ) site. Although [2 ] + is stereochemically rigid on the NMR timescale, spin-saturation transfer experiments implicate reversible dissociation of the Fe–CH2 bond, allowing interchange of all three diastereoisomers. Using 13 CH2 O, the methylenation begins with formation of [Fe2 [(μ-SCH2 )2 N 13 CH2 OH](CO)4 (PMe3 )2 ] + . Protonation converts this hydroxymethyl derivative to [2 ] +, concomitant with 13 C-labelling of all three methylene groups. The Fe–CH2 N bond in [2 ] + is electrophilic: PPh3, hydroxide, and hydride give, respectively, the phosphonium [Fe2 [(μ-SCH2 )2 NCH2 PPh3 ](CO)4 (PMe3 )2 ] +, 1, and the methylamine Fe2 [(μ-SCH2 )2 NCH3 ](CO)4 (PMe3 )2 . The reaction of [Fe2 [(μ-SCH2 )2 NH](CN)2 (CO)4 ] 2− with CH2 O/HBF4 gave [Fe2 [(μ-SCH2 )2 NCH2 CN](CN)(CO)5 ] − ([4 ] − ), the result of reductive elimination from [Fe2 [(μ-SCH2 )2 NCH2 ](CN)2 (CO)4 ] − . The phosphine derivative [Fe2 [(μ-SCH2 )2 NCH2 CN](CN)(CO)4 (PPh3 )] − ([5 ] − ) was characterized crystallographically.